Development of Simulator for Smart Anti-Flooding Systems: Fostering Hands-On Learning in University Education - Muhida, Riza; Riza, Muhammad; Murwadi, Haris; Nurhasanah, Any; Legowo, Ari; Harsoyo, Agung (Master Program in Mechanical Engineering, Gunadarma University, 2025)
The Flooding remains one of the most challenging natural disasters, causing widespread damage and disruption across urban and rural areas. As the frequency and intensity of floods increase due to climate change and urbanization, there is a growing need for effective flood management systems. This paper presents the development of a **Smart Anti-Flooding System (SAFS)** simulator designed to enhance hands-on learning for university students, particularly in engineering, disaster management, and environmental science programs. The SAFS integrates sensors, microcontrollers, pumps, and photovoltaic (PV) panels into an autonomous flood management system, offering students the opportunity to bridge the gap between theoretical knowledge and real-world application. The simulator monitors water levels using ultrasonic and level sensors, while controlling pumps and servo motors based on real-time data, enabling automatic water redirection in flood-prone areas. Powered by renewable energy, the system incorporates sustainability into flood management, making it a relevant tool for both education and disaster resilience. This paper highlights the SAFS's integration into university curricula, the learning outcomes achieved, and feedback from students who used the system. The results indicate that the simulator significantly enhances students' practical skills, fosters collaboration, and promotes a deeper understanding of disaster management through experiential learning